Effect of organic manure fertilizer on the growth of Macaranga gigantea - Dwi Susanto; AULIANA; RATNA KUSUMA; RUDIANTO AMIRTA (Nusantara Bioscience, 2019)
Abstract. Susanto D, Auliana, Kusuma R, Amirta R. 2019. Effect of organic manure fertilizer on the growth of Macaranga gigantea. Nusantara Bioscience 11: 166-171. M. gigantea planting research has been conducted in several habitats such as natural forest gaps, drained peatland and soil with highly degraded land for rehabilitation. This study investigated the effect of organic manure fertilization on soil, tissue chemical properties and growth performance of Macaranga gigantea planted at dense space of 2,5 m x 2,5 m. The experiment used a randomized block design with treatment of fertilization using goat manure with five gradual concentrations namely P0 (0 g), P1 (100 g), P2 (200 g), P3 (300 g) and P4 (400 g) in which each treatment consisted of three groups with 20 replications for each group, totaling 300 seedlings observed. The results showed that organic manure fertilization promoted stem height, stem diameter, leaf number and nutrient concentrations in the leaves of four-month-old M. gigantea. The best growth performance was gained from the treatment of P3 (300 g), followed by P2, P1, P4, and P0. The highest nutrient contained in leave tissue was potassium, followed by calcium, magnesium, nitrogen and available phosphorus.